Consumption of Seafood, Serum Liver Enzymes, and Blood Levels of PFOS and PFOA in the Japanese Population. Issue 3 (4th October 2013) - Yamaguchi, Miwa; Arisawa, Kokichi; Uemura, Hirokazu; Katsuura‐Kamano, Sakurako; Takami, Hidenobu; Sawachika, Fusakazu; Nakamoto, Mariko; Juta, Tomoya; Toda, Eisaku; Mori, Kei; Hasegawa, Manabu; Tanto, Masaharu; et al.
Abstract : Consumption of Seafood, Serum Liver Enzymes, and Blood Levels of PFOS and PFOA in the Japanese Population: Miwa YAMAGUCHI, et al . Department of Preventive Medicine, Institute of Health Biosciences, the University of Tokushima Graduate School, Japan— Objective: Perfluorooctanesulfonate (PFOS) and perfluorooctanoate (PFOA) have been shown to accumulate in the human body. The purpose of the present study was to examine the factors associated with the blood levels of PFOS and PFOA. Methods: A cross‐sectional study was performed on 307 men and 301 women (aged 16−76 years) living in 15 prefectures in Japan. Blood levels of PFOS and PFOA were measured by liquid chromatography‐mass spectrometry. Hepatic enzymes (γ‐GTP, GOT, and GPT) and ω‐3 polyunsaturated fatty acids (DHA and EPA) levels in serum were also measured. Associations between the levels of PFOS and PFOA in blood and the intake frequency of 41 kinds of dishes, foods and beverages and the serum levels of liver enzymes and ω‐3 polyunsaturated fatty acids were examined using rank correlations. Results: Frequency of intake of boiled fish in broth, sliced raw fish and coastal fish showed significant positive correlations with PFOS concentrations in blood after adjustments for potential confounders. Serum levels of GOT, GPT, DHA and EPA showed significant positive correlations with PFOS and PFOA in blood. There was also a significant regional difference in the blood levels of PFOS and PFOA, with medians being highest in the Tokai/Hokuriku/ Kinki region. Conclusions: These findings suggest that the concentrations of PFOS in blood were mainly associated with fish consumption and that the levels of PFOS and PFOA were associated with the serum levels of liver enzymes in Japanese populations. Further investigations are required to clarify the reason for the regional differences in blood levels of PFOS and PFOA in Japan.